Penerapan Model Pembelajaran Kooperatif Tipe Snowball Throwing Terhadap Hasil Belajar Struktur Atom Kelas X Di SMA Negeri 1 Marawola - Irna Vidianawati; Suherman Suherman; Vanny Maria Tiwow (Jurnal Akademika Kimia, 2014)
One of the indicators of the successful is the reachment of the students’ learning outcome on every subject taught belong to chemistry subject. This research conducted at SMA Negeri 1 Palu Marawola with the purpose of determining the difference of students’ learning outcome on chemistry subject which treated with cooperative learning model snowball throwing type with convensional learning on the material of atomic structure of the tenth grade students in SMA Negerei 1 Marawola. The population of the research was the tenth grade students in academic year 2013/2014. The sample was the Class E as the experimental class numbered 25 students and Class D as the control class numbered 25 students. The technique of data collection done through achievement test on chemistry subject particularly on atomic structure validated at first. The result of testing used two tailed t-test statistics analysis with prerequisite that is normality and homogenity tests. The data analysis result obtained the average score on experimental class = 75.04 and for the control class the average score obtained = 68. Based on the hypothesis with two tailed t test statistics it obtained the value of t counted =7.45 and t table = 2.02 at α = 0.05. In this case H1 was accepted and H0 was rejected because t counted was on the area of H0 rejection. It showed that there was a difference of students’ learning outcome through the application of cooperative learning snowball throwing type and convensional of the tenth grade students of SMA Negeri 1 Marawola.